Genetic control of mitochondrial malate dehydrogenases: evidence for duplicated chromosome segments. - Yang, N S (1977)
The genetic control of the major mitochondrial isoenzymes of malate dehydrogenase (L-malate:NAD+ oxidoreductase; EC 1.1.1.37) has been investigated in Zea mays. The mitochondrial isozymes are coded at four nuclear gene loci. Two of the loci (mdh1 and mdh2) are diallelic and tightly linked. The other two loci (mdh3 and mdh4) appear to have arisen by duplication of the chromosome segment carrying mdh1 and mdh2, but are not linked to them. The segregation of such a duplicate segment can explain anomalous backcross and F2 segregation ratios.